Orbital Inflammatory Disease in Relapsing Polychondritis. (August 2014) - Teo, Livia; Choo, Chai Teck
Abstract We present a 73-year-old Chinese male with bilateral relapsing, remitting orbital inflammatory disease associated with relapsing polychondritis. He first presented with right orbital inflammation that did not improve despite antibiotic treatment. Computer tomography (CT) of the orbits showed a soft tissue mass along the roof of the orbit, which was biopsied, revealing acute on chronic inflammation. There was complete resolution of his orbital inflammation within 2 weeks of initiating systemic steroid treatment. He subsequently developed recurrent bouts of left orbital inflammation. One year later, he was diagnosed with relapsing polychondritis and subsequently developed multiple myeloma seven years later. Comanagement with a rheumatologist will be helpful to achieve control of the disease with judicious use of immunosuppression. Long-term follow-up of the patient will be necessary to monitor for malignant transformation of the orbital lesion, as well as the development of other hematologic malignancies.